Morning Briefing Meetings as a Strategy to Improve Healtcare Workforce and Service Quality Management at the Puskesmas Pembantu Lubang Buaya Jakarta Timur - Nurmalita Sari, Hermina; Supriyadi, Supriyadi; Zaharuddin, Zaharuddin (International Journal of Business, Law, and Education, 2025)
This study evaluates the impact of morning briefing meetings on communication effectiveness, job satisfaction, and service quality at the Lubang Buaya Health Center. Using a quantitative descriptive-analytical method, data were collected from five health workers through structured questionnaires and analyzed with SPSS Version 20. The findings reveal that while morning briefings moderately improved team communication effectiveness (mean = 19.2), their effect on job satisfaction and service quality was not statistically significant. Regression analysis showed that morning briefings accounted for 34% of the variability in job satisfaction but failed to significantly influence service quality or workforce improvement (p > 0.05). Normality tests confirmed the data’s suitability for parametric analysis. Despite positive correlations, the results suggest that morning briefings alone are insufficient to significantly enhance healthcare outcomes, emphasizing the need for additional strategies to improve health worker performance and service delivery.